Răspuns :
(49 + 5 × a) : 9 + 89 = 100
(49 + 5 × a) : 9 = 100 - 89
(49 + 5 × a) : 9 = 11
49 + 5 × a = 11 × 9
49 + 5 × a = 99
5 × a = 99 - 49
5 × a = 50
a = 50 : 5
a = 10
(49 + 5 × a) : 9 = 100 - 89
(49 + 5 × a) : 9 = 11
49 + 5 × a = 11 × 9
49 + 5 × a = 99
5 × a = 99 - 49
5 × a = 50
a = 50 : 5
a = 10
(49 + 5 × a) : 9 + 89 = 100
(49 + 5 × a) : 9 = 100 - 89
(49 + 5 × a) : 9 = 11
49 + 5 × a = 11 × 9
49 + 5 × a = 99
5 × a = 99 - 49
5 × a = 50
a = 50 : 5
a = 10
rs:10
(49 + 5 × a) : 9 = 100 - 89
(49 + 5 × a) : 9 = 11
49 + 5 × a = 11 × 9
49 + 5 × a = 99
5 × a = 99 - 49
5 × a = 50
a = 50 : 5
a = 10
rs:10